Politeness Maxim Used By Characters in Forever My Girl Movie - Purnami, Ni Putu Mega; Qomariana, Yana; Mas Indrawati, Ni Luh (Udayana Journal of Social Sciences and Humanities; Vol 6 No 1 (2022): UJoSSH, February 2022DO - 10.24843/UJoSSH.2022.v06.i01.p07, 2022)
Maxim is a linguistic rule in lingual interaction between the speaker and the interlocutor. Politeness maxim is an important aspect that contributes in maintaining the social harmony.  This study is entitled Politeness Maxim Used by The Characters in “Forever My Girl” movie. Q ualitative research is used in this study. The aims in this study are to find what maxim are performed in utterance used by the characters and what scale of politeness shown by the characters in the movie. The both theories applied are based on Leech theory (1983) which are politeness maxim and the scale of politeness. The data were collected by using documentation method and note-taking technique. In the result shows that there are six types of politeness maxim and the researcher found each types of politeness scale. The most commonly maxim used is Agreement Maxim and the dominant scale is social distance.